Factors Associated with Islamic Behavior Among Thai Muslim Youth in the Three Southern Border Provinces, Thailand - Laeheem, Kasetchai (Kasetsart Journal of Social Sciences, 2014)
The purpose of this research was to examine the factors associated with Islamic behavior of Thai Muslim youth in the three southern border provinces whose behavior was in accordance with the Islamic religion. In total, 2,160 Thai Muslim youths in the three southern border provinces were interviewed using questionnaires to collect relevant data. Data analysis using the R Program software was employed using frequency distribution, percentage, Pearson’s chi-squared test, odd ratios and logistic regression to investigate the independent associations between the predictor variables and the outcomes. We found that 31.7 percent of Thai Muslim youth reported that their behavior was in accordance with the Islamic religion. Islamic behavior was significantly associated with the level of knowledge of the religion, the level of the Islamic way of upbringing children, participation in Islamic religious activities, and participation in Islamic religious training. Thai Muslim youth who were more likely to express Islamic behavior had: a high level and a moderate level of the Islamic way of upbringing children (12.10 and 3.41 times, respectively); a high level and a moderate level of knowledge of Islamic religion (3.61 and 2.00 times, respectively); participated in Islamic religious activities regularly and occasionally (3.45 and 2.35 times, respectively); and participated in Islamic religious training regularly and occasionally (2.99 and 1.93 times, respectively).